Evaluation of Village-Owned Enterprise (BUMDes) Financial Management in Supporting Village Own-Source Revenue: A Case Study of BUMDes in Kerinci Regency - Zachari Abdallah; Nurapni Jami Putri; Maryanto Maryanto (The Future of Education Journal, 2026)
This study aims to analyze the alignment of financial management principles and governance in Village-Owned Enterprises (BUMDes) in Kerinci Regency, as well as to measure the contribution of BUMDes dividends to Village Original Income (PADes). Utilizing a mixed-methods approach with a sequential explanatory strategy, this study examined a sample of 30 BUMDes selected through stratified purposive sampling based on their business development stages (Advanced, Developing, and Emerging categories). The evaluation was based on five key indicators: planning and budgeting, transaction bookkeeping, reporting and accountability, operational efficiency (operating ratio), and governance score. The results reveal a significant performance gap in both financial metrics and governance across the BUMDes categories. The Advanced category (n=5) achieved the highest performance, with an average annual revenue of IDR 519,000,000, a net profit of IDR 198,747,000, and a governance score of 92.6, dominating PADes contributions at 85.8% (an average of IDR 58,000,600/year). The Developing category (n=15) recorded an average revenue of IDR 103,800,000, a net profit of IDR 23,946,000, and a governance score of 73.5, contributing 14.2% to PADes (an average of IDR 3,200,000/year). Meanwhile, the Emerging/Passive category (n=10) demonstrated the lowest performance, with an average revenue of IDR 17,100,000, a net profit of IDR 1,021,000, a governance score of 49.8, and a 0% contribution to PADes.